PELATIHAN PEMANFAATAN LIMBAH KULIT PISANG SEBAGAIBAHAN DASAR PEMBUATAN KERUPUK - Arif Hartono (UII, 2013)
Banana skin is a waste material (waste bananas) are quite numerous. Banana peelwaste contains nutrients is high quite, especially in vitamins and minerals that can beused as food ingredients. Besides its use as a raw material of food, improving nutritionalvalue when processed into food. One of the banana skin processed foods are crackers.Where is the way the process is not quite difficult facilitate the villagers to practice itourselves. So the banana skin that was not originally utilized as a marketable andvaluable benefits.